Synthesis and Biological Evaluation of 2-methyl-1Hbenzimidazole and 1H-benzimidazol-2-yl-methanol - Poddar, Saikat Kumar; Saqueeb, Nazmus; Rahman, SM Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Two benzimidazole derivatives namely 2-methyl-1H-benzimidazole (1) and 1H-benzimidazol-2- ylmethanol (2) were synthesized in high yields by condensing O-phenylenediamine with two different carboxylic acid derivatives: glacial acetic acid and glycolic acid, following a different synthetic protocol. Structures were elucidated by spectroscopic methods. Among the two benzimidazole derivatives synthesized, 2-methyl-1Hbenzimidazole (1) showed moderate antioxidant activity with IC50 values of 144.84?g/ml whereas 1H-benzimidazol- 2-ylmethanol (2) displayed mild antioxidant activity (IC50 value 400.42 ?g/ml). Compound 1 also exhibited prominent cytotoxic activities with the LC50 value of 0.42 ?g/ml when compared to the standard vincristine sulphate (LC50 value of 0.544 ?g/ ml). It also demonstrated weak antimicrobial activity having 7-8 mm of zone of inhibition. Dhaka Univ. J. Pharm. Sci. 15(1): 83-87, 2016 (June)